2008
DOI: 10.1123/apaq.25.2.95
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity of Youth with Intellectual Disability: Review and Research Agenda

Abstract: This review characterizes physical activity behavior in youth with intellectual disability (ID) and identifies limitations in the published research. Keyword searches were used to identify articles from MEDLINE, EBSCOhost Research Databases, Psych Articles, Health Source, and SPORT Discus, and ProQuest Dissertations and Theses up to June 2007. Data were extracted from each study using a template of key items that included participant population, study design, data source, and outcome measure. Nineteen manuscri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
127
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(138 citation statements)
references
References 50 publications
7
127
0
4
Order By: Relevance
“…It is well documented that youth with intellectual disabilities are less active than peers without disabilities, 3 however there are few published efforts to improve physical activity in this population segment. This review illustrates that both the quantity and quality of physical activity interventions for youth with intellectual disabilities are lacking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well documented that youth with intellectual disabilities are less active than peers without disabilities, 3 however there are few published efforts to improve physical activity in this population segment. This review illustrates that both the quantity and quality of physical activity interventions for youth with intellectual disabilities are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…In 2008, we published a review paper that aimed to summarize and critically analyze the existing literature on physical activity of youth with intellectual disabilities. 3 At that time, findings were variable with evidence to support that children with intellectual disabilities were less active, more active, and similarly active than their typically developing peers. We reported that significant methodological limitations and small sample sizes restricted the conclusions that could be drawn about the physical activity behavior of youth with intellectual disabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been reported that youth with physical (e.g., cerebral palsy) and sensory (e.g., limited visual capacity) disabilities engage in less recreational activities than their peers without disabilities (Longmuir & Bar-Or, 2000), little is known about the physical activity patterns of youth with ID (Fernhall & Unnithan, 2002;Frey et al, 2008;Rimmer and Rowland, 2008). The use of pedometry could provide insight into their physical activity patterns.…”
Section: Discussionmentioning
confidence: 99%
“…The critical need for such research specific to youth with disabilities was ably addressed in two recent articles (Frey, Stanish, & Temple, 2008;Rimmer & Rowland, 2008). In the article by Rimmer and Rowland (2008) it was stated, "One of the most important challenges for paediatric rehabilitation and healthcare professionals is finding ways to increase physical activity and fitness among youth with disabilities in community-based settings" (p. 141).…”
mentioning
confidence: 99%
See 1 more Smart Citation